Sosialisasi dan Pelatihan Teknik dan Tata Cara Pengukuran Antropometri Bagi Peneliti di Pusat Riset Teknologi Pengujian dan Standar, Badan Riset dan Inovasi Nasional (BRIN) - TIUAJ, yanto; Prasetya, Wibawa; Taruna, Malvin; Pusung, Kevin Pusung; Angelina, Angelina; Wicaksono, Michael Hizkia (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2022)
The activity aimed to provide knowledge about anthropometry and the measurements illustration for researchers in the Pusat Riset Teknologi Pengujian dan Standar (PRTPS – BRIN). During workshop, the participants were provided with the basic knowledge of anthropometry, standardization of measurement, measurement illustrations and how to apply such data for design, in particular for school furniture design. In addition, the participants were also demonstrated the use of instruments in the laboratory. In this workshop, 15 researchers participated in both workshop and instrument demonstration.